A Study on Students’ Difficulties In Vocabulary Mastery at First Grade Students of SMPN 1 Baula - Bimas Reskiawan; Netty Huzniati Andas; Hajra Hajra (Fakultas Sastra - Universitas Muslim Indonesia, 2020)
The Objective of the research were to know difficulties of the students in vocabulary mastery and to find out factors cause students difficulties in vocabulary mastery. This Research employed a qualitative research design, For gaining the data, the researcher used questionnaire and interview. This research was conducted by interviewed 3 students appointed by the teacher. This means students have the same opportunity to be chosen as a person participants. In this research, researchers had 20 participants. The researcher gave a questionnaire for participants. Because this research has a purpose to find out the difficulties of students in vocabulary mastery. Second grade students at SMPN 1 Baula still have a lot of difficulties in vocabulary mastery. Based on aspects of the questionnaire and interview, namely pronunciation the word, spelling the word, and the word meaning. Furthermore, the difficulties can be caused by many factors. There are several factors that cause students difficulties in vocabulary mastery : (1) different between written word and the pronouncing in English (2) rarely to interact using English, it's rarely to practice, (3) the writing the word or sound-spelling mismatches (4) some word similar but different meaning, (5) wrong pronunciations are often caused by a lack of similarity between sounds English and Indonesian.